Gene Signatures of NEUROGENIN3+ Endocrine Progenitor Cells in the Human Pancreas - Yong, Hyo Jeong; Xie, Gengqiang; Liu, Chengyang; Wang, Wei; Naji, Ali; Irianto, Jerome; Wang, Yue J. (Frontiers in Endocrinology, 2021)
NEUROGENIN3+ (NEUROG3+) cells are considered to be pancreatic endocrine progenitors. Our current knowledge on the molecular program of NEUROG3+ cells in humans is largely extrapolated from studies in mice. We hypothesized that single-cell RNA-seq enables in-depth exploration of the rare NEUROG3+ cells directly in humans. We aligned four large single-cell RNA-seq datasets from the postnatal human pancreas. Our integrated analysis revealed 10 NEUROG3+ epithelial cells from a total of 11,174 pancreatic cells. Noticeably, human NEUROG3+ cells clustered with mature pancreatic cells and epsilon cells displayed the highest frequency of NEUROG3 positivity. We confirmed the co-expression of NEUROG3 with endocrine markers and the high percentage of NEUROG3+ cells among epsilon cells at the protein level based on immunostaining on pancreatic tissue sections. We further identified unique genetic signatures of the NEUROG3+ cells. Regulatory network inference revealed novel transcription factors including Prospero homeobox protein 1 (PROX1) may act jointly with NEUROG3. As NEUROG3 plays a central role in endocrine differentiation, knowledge gained from our study will accelerate the development of beta cell regeneration therapies to treat diabetes.